Ang II–AT1R Increases Cell Migration Through PI3K/AKT and NF‐κB Pathways in Breast Cancer. Issue 11 (November 2014) - Zhao, Yanbin; Wang, Hongbin; Li, Xiuli; Cao, Mengru; Lu, Hailing; Meng, Qingwei; Pang, Hui; Li, Hailin; Nadolny, Christina; Dong, Xiaoqun; Cai, Li
<x xml:space="preserve">Abstract</x> Angiotensin II (Ang II), a biologically active peptide of the renin–angiotensin system (RAS), plays an important role in promoting cell migration via Angiotensin II type 1 receptor (AT1R). In this study, we examined the mechanisms by which Ang II affected cell migration in AT1R‐positive MDA‐MB‐231 human breast cancer cells. Ang II increased cell migration and expression of matrix metalloproteinase (MMP)‐2, ‐9 in a dose‐dependent manner. Ang II‐mediated cell migration was reduced by specific blocking of MMP‐2 and MMP‐9, as well as with pretreatment with inhibitors of AT1R, phosphatidylinositol 3‐kinase (PI3K), Akt, and NF‐κB. Similarly, Ang II‐mediated expression of MMP‐2, ‐9 was downregulated by pretreatment with inhibitors of AT1R and PI3K. In addition, Ang II treatment significantly induced phosphorylation of PI3K, Akt, and resulted in increased NF‐κB activity. These findings suggest that Ang II activates the AT1R/PI3K/Akt pathway, which further activates IKKα/β and NF‐κB, resulting in enhanced expression of MMP‐2, ‐9 and migration in human breast cancer cells. Therefore, targeting Ang II/AT1R/PI3K/Akt/NF‐κB signaling could be a novel anti‐metastatic therapy for breast cancer. J. Cell. Physiol. 229: 1855–1862, 2014. © 2014 Wiley Periodicals, Inc.